2004
DOI: 10.1111/j.1365-2095.2004.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of dietary lipid level and temperature on growth, body composition and fatty acid profile of rohu, Labeo rohita (Hamilton)

Abstract: Three isonitrogenous (320 g kg−1 crude protein, casein and gelatine) semi‐purified diets with 80 (L8), 130 (L13) and 180 (L18) g kg−1 lipid (sunflower oil at increasing levels and cod liver oil fixed at 50 g kg−1) at three digestible energy levels (12 096, 13 986 and 15 876 kJ kg−1 dry weight) and were tested, in triplicate, on rohu fingerlings (3.2 ± 0.08 g) at two different temperatures (21 and 32 °C). Fish were fed to apparent satiation, twice daily, at 09.00 and 15.00 h, 7 days a week for 56 days. Maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
(55 reference statements)
5
23
1
Order By: Relevance
“…Thus in the present study four individual algae were incorporated in the diet replacing 40% of the control diet and one complete algal meal mixture were tested to find out their suitability for inclusion in the rohu diet. Mishra and Samantaray (2004) observed maximum growth of 481.8% in rohu using 32% protein at 3 digestible energy level (12 096, 13 986 and 15 876 kJ/kg of feed). Chittem and Kunda (2013) used 20 g protein and 337 kcal/100 g of feed to study the effect of n-3 fatty acid on rohu and observed maximum weight gain of 127.4%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus in the present study four individual algae were incorporated in the diet replacing 40% of the control diet and one complete algal meal mixture were tested to find out their suitability for inclusion in the rohu diet. Mishra and Samantaray (2004) observed maximum growth of 481.8% in rohu using 32% protein at 3 digestible energy level (12 096, 13 986 and 15 876 kJ/kg of feed). Chittem and Kunda (2013) used 20 g protein and 337 kcal/100 g of feed to study the effect of n-3 fatty acid on rohu and observed maximum weight gain of 127.4%.…”
Section: Discussionmentioning
confidence: 99%
“…From the present study it appears that the level of n-3 PUFA available from some algal diets, particularly WS and NS, is sufficient to meet the requirement of the same in rohu. In rohu an increased level of accumulation of EPA and arachidonic acid (20:4n6) over their respective initial level in liver and muscle at 21°C and 32°C suggested bio-transformation of the parent FAs of these series (Samantaray and Mishra, 2004). Karanth et al (2009) reported high deposition of linolenic acid (18:3n3) and EPA in rohu liver feeding with high linolenic acid diet.…”
Section: Fattymentioning
confidence: 99%
See 2 more Smart Citations
“…Several research works carried on marine fish species have confirmed that the dietary levels directly influence the fatty acid profile of fish (Stickney and Hardy, 1989;Brown et al, 1997). However, very little information is available on the same aspect in case of freshwater fish species (De Silva et al, 1997;Mishra, 2000;Mishra and Samantaray, 2004).…”
Section: Introductionmentioning
confidence: 99%